1998
DOI: 10.1111/j.1349-7006.1998.tb00536.x
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Squamous Cell Carcinomas in the Salivary Glands of Rats by Potassium Iodide

Abstract: In a 2-year carcinogenicity study of potassium iodide (KI) in F344/DuCrj rats, squamous cell carcinomas (SCCs) were observed in the salivary glands of 4/40 males and 3/40 females receiving 1000 ppm KI in the drinking water. Ductular proliferation with lobular atrophy was observed at high incidence in the submandibular glands of the high-dose animals, and squamous metaplasia was frequently evident within the proliferative ductules and the larger interlobular ducts. A transition from metaplasia to SCC was appare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 19 publications
1
12
0
Order By: Relevance
“…The transformation of squamous metaplasia into squamous cell carcinoma cannot be excluded and should be considered in determining the prognosis. 41 Close monitoring of the patient and a review conducted at 18 months postoperatively confirmed no recurrence and no development of malignant change. Further, it seems that the persistent pleomorphic adenoma in the patient's lower lip was a major factor contributing to the severe gingival recession around lower central incisors.…”
Section: Discussionmentioning
confidence: 81%
“…The transformation of squamous metaplasia into squamous cell carcinoma cannot be excluded and should be considered in determining the prognosis. 41 Close monitoring of the patient and a review conducted at 18 months postoperatively confirmed no recurrence and no development of malignant change. Further, it seems that the persistent pleomorphic adenoma in the patient's lower lip was a major factor contributing to the severe gingival recession around lower central incisors.…”
Section: Discussionmentioning
confidence: 81%
“…On the other hand, it has been reported that intake of high doses of I Ϫ can promote cancer in animals. 33) In the present study, I Ϫ efficiently inhibited the reaction of nucleosides, especially dG, with the myeloperoxidase-H 2 O 2 -Cl Ϫ system. However, since the plasma concentration of I Ϫ is low (0.46-0.67 mM), 16) it is unlikely that I Ϫ affects nucleoside damage caused by myeloperoxidase in plasma.…”
Section: Brmentioning
confidence: 97%
“…Squamous cell metaplasia was induced with chlorodibromomethane in F344 rats but not in B6C3F1 mice after 13-week treatment, but no tumor progression was noted after 2 years treatment ( Dunnick et al 1985 ). On the other hand, transition of squamous metaplasia into squamous cell carcinoma in the submandibular gland via a non-genotoxic, proliferation-dependent mechanism was postulated after 2-year treatment with potassium iodide in F344 rats ( Takegawa et al 1998 ). In addition, in experiments with implanted sponge pellets containing DMBA inducing squamous cell carcinomas in Sprague-Dawley rats, the authors concluded that ductal segments undergoing squamous cell metaplasia may have participated in the genesis of neoplasia during experimental carcinogenesis ( Cao et al 2000 , Sumitomo et al 1996 ).…”
Section: Salivary Glandsmentioning
confidence: 99%
“…Few carcinomas and adenocarcinomas have been reported in mice and rats ( Botts et al 1999 ; Hosokawa et al 2000 ; Nishikawa et al 2010 ; Tsunenari et al 1997 ). Malignant tumors in the salivary glands may be induced with chemical substances in rats ( Neuenschwander and Elwell 1990 ; Sumitomo et al1996 ; Cao et al 1999 ; Zaman et al 1996 ) and mice ( Botts et al 1999 ; Takegawa et al 1998 ; Takai et al 1986 ; Yura et al 1995 ) or in various transgenic animal models ( Dardick et al 2000 ; Declercq et al 2005 ; Nielsen et al 1991 ; Nielsen et al 1995 ).…”
Section: Salivary Glandsmentioning
confidence: 99%